Kritik Sanad sebagai Instrumen Verifikasi Hadis - Rahmad Sahputra; Khoirul Azmi Harahap; Zikri Darussamin (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The study of hadith is always closely related to the analysis of the sanad (chain of transmission) as a chain of narrators that connects the Prophet Muhammad (peace be upon him) and subsequent generations. With the emergence of hadith forgery, the expansion of Islamic territory, and the increasing need for hadith codification, verification of the validity of the sanad has become a major urgency in the Islamic scholarly tradition. Sanad criticism is the primary method in hadith science used to assess the level of validity and reliability of the transmission line by tracing the integrity, competence, and continuity of the narrators. This study aims to comprehensively outline the concept of sanad criticism by discussing the definition, urgency, scope, and steps used by scholars in determining the quality of a sanad. The research method used is a qualitative approach based on library research by analyzing classical and contemporary sources in the field of hadith science, particularly those related to sanad criticism. The results of the study indicate that sanad criticism functions as a scientific instrument that distinguishes authentic sanads that can be used as evidence from weak or problematic ones. The object of study covers the entire chain of narrators, taking into account aspects of fairness, accuracy of memorization, and continuity of the transmission process. The application of sanad criticism to the hadith about the virtues of fasting on Mondays and Thursdays shows that the sanad of the hadith is in the category of ḥasan li-dzātih and, with the existence of supporting lines (mutāba‘āt), approaches the quality of ṣaḥīḥ, making it worthy of being used as evidence in the practice of sunnah worship. Thus, sanad criticism not only maintains the purity of the teachings of the Prophet Muhammad SAW, but also becomes an important foundation in ensuring the validity of the hadith in the construction of Islamic law, both in the classical and contemporary eras.